Desiring occupation: Theorising the passion, creativity, and social production of everyday life. Issue 1 (2nd January 2022) - Barlott, Tim; Turpin, Merrill
ABSTRACT: In this paper, we operationalise a postmodern conceptualisation of desire in order to articulate occupation as a passionate, creative, and productive process that is entangled with the social world. Employing the philosophy of Gilles Deleuze and Felix Guattari, we use the concepts of assemblage and desire to theorise how passionate impulses are socially constructed and produce the flows of everyday life. The concept of assemblages refers to the dynamic webs of interconnection that make up our social world. The social and material elements within an assemblage (human, non-human, physical, non-physical) are continually shaping and being shaped by each other, entangled in an ongoing process of social production. In this paper, we theorise occupation as an assemblage, as a dynamic and social process that produces the flows of everyday life. The concept of desire refers to the creative impulse and passion that stirs individuals to create or act within their social world/assemblage. We present desire as a social force, one that is produced by the assemblages of everyday life and also one that produces everyday life. While the assemblages of everyday life have the potential to constrain desire, they also have the potential to creatively liberate the transformative potential of desire – generating liberating occupational flows.